Unleashing the power of internet skills towards entrepreneurship engagement among youth in Malaysia - Parvin, Ali; Omar, Siti Zobidah; Osman, Mohd Nizam; Tamam, Ezhar (Human Resource Management Academic Research Society, 2019)
The maze around Information and Communications Technology (ICT) has led youth to narrow their focus on technologies that matters in venturing into new businesses. Internet in particular offers countless of opportunities that one with efficient skills could get with promising benefit of brighter career possibilities and income expansions. The purpose of this study is to examine internet skills competency towards entrepreneurship engagement among youth in Malaysia. This study used a quantitative approach whereby 400 youths in Malaysia were selected as respondents. The study is based on non-probability sampling. The data were gathered through self-administrative questionnaire which has been written in English and Bahasa Melayu. The findings show that youth should accept and practice certain elements such as access to right information, competency in using the internet and acquiring technical skills in order to strengthen their entrepreneurial engagement. The study stresses on the need for youth to advocate and utilize internet resources as it will lead the society for development of entrepreneurial measures for new generation of internet users.